Counseling Junggringan Saintification of Ki Ageng Suryomentaram Teaching An Ideas Toward Indigenous Counseling - Sarwono, Budi; Ramli, M (Universitas Muhammadiyah Metro, 2018)
Before Indonesia Became an independent nation and declared its form to be Republic, in Reviews, those cluster of islands called the archipelago there are few independent kingdoms. One of them is the Mataram Kingdom, located in Java. As a living system, Mataram has its own culture, laws, and doctrines. One of the most widely known teachings is Junggringan, a systematic group dynamics of the which has a therapeutic effect. Junggringan was first taught by Ki Ageng Suryomentaram, son of King Mataram VIII. This paper is a scientific reconstruction of the technique of junggringan as indigenous counseling in group settings.